The 5-formyl-tetrahydrofolate proteome links folates with C/N metabolism and reveals feedback regulation of folate biosynthesis. Issue 10 (5th August 2021) - Li, Weichao; Liang, Qiuju; Mishra, Ratnesh Chandra; Sanchez-Muoz, Raul; Wang, Huan; Chen, Xin; Van Der Straeten, Dominique; Zhang, Chunyi; Xiao, Youli
Abstract: Folates are indispensable for plant development, but their molecular mode of action remains elusive. We synthesized a probe, "5-F-THF-Dayne, " comprising 5-formyl-tetrahydrofolate (THF) coupled to a photoaffinity tag. Exploiting this probe in an affinity proteomics study in Arabidopsis thaliana, we retrieved 51 hits. Thirty interactions were independently validated with in vitro expressed proteins to bind 5-F-THF with high or low affinity. Interestingly, the interactors reveal associations beyond one-carbon metabolism, covering also connections to nitrogen (N) metabolism, carbohydrate metabolism/photosynthesis, and proteostasis. Two of the interactions, one with the folate biosynthetic enzyme DIHYDROFOLATE REDUCTASE-THYMIDYLATE SYNTHASE 1 ( At DHFR-TS1) and another with N metabolism-associated glutamine synthetase 1;4 ( At GLN1;4), were further characterized. In silico and experimental analyses revealed G35/K36 and E330 as key residues for the binding of 5-F-THF in At DHFR-TS1 and At GLN1;4, respectively. Site-directed mutagenesis of At GLN1;4 E330, which co-localizes with the ATP-binding pocket, abolished 5-F-THF binding as well as At GLN1;4 activity. Furthermore, 5-F-THF was noted to competitively inhibit the activities of At DHFR-TS1 and At GLN1;4. In summary, we demonstrated a regulatory role for 5-F-THF in N metabolism, revealed 5-F-THF-mediated feedback regulation of folate biosynthesis, and identified a total of 14 previously unknown high-affinity binding cellular targets of 5-F-THF. Together, this sets a landmark toward understanding the role of folates in plant development. Abstract : Exploration of proteins that interact or bind with folates reveals folate-modulated growth and development in Arabidopsis.